Knowledge and practice of rickshaw and thela pullers on tuberculosis in Jaleshwor Municipality of Mahottari District. - Sah, Saurabh Kishor (2011)
SUMMARY: The overall objective of study was to have the base line information to understand and measure level of knowledge and practice on health seeking behavior for treatment of Tuberculosis among Rickshaw and Thela pullers. The study population was Rickshaw and thela pullers who were permanently engaged in the profession for at leat six month. study area was Jaleshwor municipality, study included 100 rickshaws and thela pullers. Interview and FGD was used as techniques of data collection where as questionnaire and checklist as tools. Nearly all 97% respondent reported having heard about TB,Among which the awareness about symptoms was good i.e. every respondent were aware of one or more symptoms. Coughing of blood i.e. 51.5% respondent agreed and regarded as major symptoms of TB 54.5% agreed that TB could transmitted through droplet infection from person to another, and 29.9% did not know about modes of transmission. 55.7% believed that any body could be infected by TB . 73.2% believed that TB could be prevented and among them 35.2% thought covering mouth and nose when coughing/ sneezing was the best option to prevent TB.the study shows that 57.7% respondent believed that sputum examination is best method for TB diagnosis, and 28.9% did not know the methods of diagnosis for TB. The study shows that 91.8% respondents believed that TB can be cured by taking specific drug given by health institution and 99% knew that TB can be treated at hospital, but only 16.5% of rickshaw and thela pullers was known to correct length of treatment i.e 6 month. A high percentages of respondent 88.7% said they did not cover their nose and mouth when coughing and sneezing , 98.9% visit hospital if feel symptoms like blood in cough, fever in evening, peristant cough and only 4.1%had been tested for TB. More than half 58.8% among 97% rickshaw and thela pullers knew people with TB,28.9% that respondent said they would keep them isolated from TB patient. and 75.3% believe that they will help TB patient for treatment but only small portion replied they would discriminate TB patient.